Are Specific Body Sites Prone for Wound Infection After Skin Surgery? A Systematic Review and Meta-Analysis. Issue 4 (19th April 2022) - Schlager, Justin Gabriel; Ruiz San Jose, Virginia; Patzer, Kathrin; French, Lars E.; Kendziora, Benjamin; Hartmann, Daniela
Abstract : Supplemental Digital Content is Available in the Text. Abstract : INTRODUCTION: Identifying risk factors for wound infection may guide clinical practice for optimal use of perioperative antibiotic prophylaxis in dermatologic surgery. OBJECTIVE: To summarize the current evidence whether specific body sites have higher risks for surgical site infections (SSI). Methods: The systematic literature search included MEDLINE, Embase, CENTRAL, and trial registers. Only observational studies qualified for inclusion and meta-analysis. We assessed the risk of bias according to the Newcastle–Ottawa Scale. RESULTS: Eighteen studies with 33, 086 surgical wounds were eligible. Eight studies were of good, 4 of fair, and 6 of poor quality. The mean infection rate was 4.08%. Meta-analysis showed that the lips had significantly higher infection rates. The lower extremity and ears had or tended toward a higher risk for infection, but studies were clinically heterogeneous. A large prospective trial found that surgical wounds on the hands were at higher risk for infection. The trunk showed the lowest infection rate. The risk for SSI in other body locations was not different or remained uncertain because of substantial heterogeneity among studies. CONCLUSION: Lips, lower extremities, and probably ears and hands may have a higher risk for wound infection after skin surgery. The trunk showed the lowest infection rate.